A Gesture Recognition Algorithm for Hand-Assisted Laparoscopic Surgery. - López-Casado, Carmen; Bauzano-Núñez, Enrique; Rivas-Blanco, Irene; Pérez-del-Pulgar-Mancebo, Carlos Jesús; Muñoz-Martínez, Víctor Fernando (MDPI, 2019)
Minimally invasive surgery (MIS) techniques are growing in quantity and complexity to cover a wider range of interventions. More specifically, hand-assisted laparoscopic surgery (HALS) involves the use of one surgeon’s hand inside the patient whereas the other one manages a single laparoscopic tool. In this scenario, those surgical procedures performed with an additional tool require the aid of an assistant. Furthermore, in the case of a human–robot assistant pairing a fluid communication is mandatory. This human–machine interaction must combine both explicit orders and implicit information from the surgical gestures. In this context, this paper focuses on the development of a hand gesture recognition system for HALS. The recognition is based on a hidden Markov model (HMM) algorithm with an improved automated training step, which can also learn during the online surgical procedure by means of a reinforcement learning process.
Keywords: Laparoscopia; Cirugía - Innovaciones tecnológicas; Aprendizaje automático (Inteligencia artificial); Surgical robotics; Machine learning; Gesture recognition